Analisis Soal HOTS Materi Asam Basa Untuk Mengukur Keterampilan Berpikir Kritis Dengan Rasch Model - Luluk Kamilia (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
One of the competencies that must be mastered to face global competition in the 21st century world of work is individuals who have critical thinking skills. Critical thinking is one form of HOTS application. The purpose of this study was to analyze the HOTS test instrument to measure critical thinking skills. The method used is Research and Development which is reduced to 3D (define, design, development). The subjects in this study were students of class XI MIPA MAN 2 Wonosobo, with data collection techniques namely interviews, tests and questionnaires. The data analysis technique in this study was validation by experts and analysis with the Rasch model assisted by Ministep software. Analyzes with the Rasch model include summary statistics, item fit, item size, item correlation, and person size. Validation from experts gets an average score of 140 out of 160 with an average proportion of 87.7% which indicates a very valid instrument. Summary statistics for the testing phase show that the measurement of the person is 0.69 and 0.73 and the measurement of the item is 0.86 and 0.87, which means that the consistency of the student's answers is in the sufficient category, but the quality of the items is good. For the person measure implementation test stage it showed 0.69 and 0.74 meaning that the consistency of student answers was also in the sufficient category, while the quality of the items for the reliability aspect was in the special category with values ​​of 0.96 and 0.97. Item Fit or the level of adding item items shows a 100% fit item from the testing stage to implementation.